An Analysis of Imperative Sentences in Sumbawanese - Novi Yuniarsi; Supriadin Supriadin; Rahmawati Rahmawati (Muhammadiyah University of Mataram, 2019)
This research aimed to investigate the imperative sentences in Sumbawanese used by the participats in informal conversation based on the types, functions, and markers. This research was conducted in Empang Subdistric especially in Cempaka Putih Village with ten participants. In conducting this research, the researcher used qualitative and the data were taken through observation, video recorder, and note taking. This research found that the types of imperative sentences in Sumbawanese are positive and negative imperative sentences. Positive imperative sentences divided into two such as positive imperative sentences with a noun as a direct address and positive imperative sentences without a noun as a direct address. While one is also divided into two, there are negative imperative sentences with a noun as a direct address and negative imperative sentence without a noun as a direct address. From all of the types of imperative sentences, the participants tend to use the positive imperative sentences with a noun as a direct address as their daily sentences in conversation. It also found that there are seven functions of imperative sentences in Sumbawanese such as imperative sentences as command, imperative sentences as request, imperative sentences as invitation, imperative sentences as suggestion, imperative sentences as advice, imperative sentences as prohibition, and imperative sentences as compulsion. However, the participants tend to use the imperative sentences as command in their conversation.